Knee extensor training in patients with patellofemoral pain: a systematic review and synthesis - Gunhamn, Ted; Pojskic, Haris; Augustsson, Sofia Ryman (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveThis systematic review and synthesis aimed to describe the frequency and characteristics of knee extensor exercise prescriptions within patellofemoral pain (PFP) interventions and to assess the extent to which key training variables are reported. By doing so, it sought to inform and support more transparent and standardized reporting practices in exercise-based rehabilitation for individuals with PFP.MethodThis systematic review was conducted following PRISMA guidelines. A literature search was performed in January 2024 across Web of Science, PubMed, Scopus, CINAHL, and SportDiscus. Studies were included if they investigated interventions incorporating knee extensor exercises for PFP.ResultsSeventy-nine studies met the inclusion criteria. The most commonly prescribed exercises were the straight leg raise, squat, and open-chain knee extension, typically performed as three sets of ten repetitions with bodyweight resistance. However, key training variables such as range of motion and intensity were often inadequately reported, limiting reproducibility and clinical applicability.ConclusionKnee extensor training for PFP predominantly consists of low-load, moderate-volume exercises, differing from conventional strength training recommendations. The lack of detailed reporting on critical variables, such as intensity and range of motion, reduces the clarity and applicability of rehabilitation protocols. Standardized reporting and further research are needed to optimize exercise prescription for PFP management.